Precise in situ etch depth control of multilayered III−V semiconductor samples with reflectance anisotropy spectroscopy (RAS) equipment - Kleinschmidt, Ann-Kathrin; Barzen, Lars; Strassner, Johannes; Doering, Christoph; Fouckhardt, Henning; Bock, Wolfgang; Wahl, Michael; Kopnarski, Michael (Beilstein Journal of Nanotechnology, 2016)
Reflectance anisotropy spectroscopy (RAS) equipment is applied to monitor dry-etch processes (here specifically reactive ion etching (RIE)) of monocrystalline multilayered III–V semiconductors in situ. The related accuracy of etch depth control is better than 16 nm. Comparison with results of secondary ion mass spectrometry (SIMS) reveals a deviation of only about 4 nm in optimal cases. To illustrate the applicability of the reported method in every day settings for the first time the highly etch depth sensitive lithographic process to form a film lens on the waveguide ridge of a broad area laser (BAL) is presented. This example elucidates the benefits of the method in semiconductor device fabrication and also suggests how to fulfill design requirements for the sample in order to make RAS control possible.
Keywords: broad area semiconductor lasers (BAL); dry-etch monitoring (RIE); precise etch depth control; reflectance anisotropy spectroscopy (RAS); III–V semiconductors